A Conformal Phased Array with Low Profile and Wide-Scanning Performance for SAR Application - Runzhi Tang; Senlin Lu; Shiwei Qu; Shiwen Yang (International Journal of Antennas and Propagation)
A low-profile wide-scanning conformal phased array (CPA), with cavity-backed stacked patch elements, is presented in this paper. To reduce the array profile, a partially dielectric-filled cavity is employed in each element, and to enhance its scanning performance, the cavity walls are deliberately modified. Finally, the designed element operates in a frequency band of 1.45∼1.75 GHz, with a profile of 0.086 λh (λh is the free-space wavelength at 1.75 GHz), and achieves ±60° scanning in the E/H-planes, with the reflection coefficient below −7 dB. The proposed design method and all numerical results are experimentally verified by a 4 × 4 CPA prototype.